2018
DOI: 10.1186/s12866-018-1318-1
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the impact of flhF inactivation on Campylobacter jejuni colonization of chick and mice gut

Abstract: BackgroundCampylobacter jejuni (C. jejuni) is a leading cause of foodborne gastroenteritis worldwide. This bacterium lacks many of the classical virulence factors, and flagellum-associated persistent colonization has been shown to be crucial for its pathogenesis. The flagellum plays a multifunctional role in C. jejuni pathogenesis, and different flagellar elements make diverse contributions. The flhF gene encodes the flagellar biosynthesis regulator, which is important for flagellar biosynthesis. In this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 54 publications
(85 reference statements)
0
6
0
Order By: Relevance
“… 133 In addition to their function in bacterial motility, C. jejuni utilizes flagella for protein secretion, biofilm formation, and adhesion. 134 , 135 Flagellar motility of C. jejuni is associated with a chemotaxis system, which is essential for effective colonization in the avian and mammalian guts. C. jejuni displays a chemotactic response to amino acids and organic acids originating from either the host or the residual gut microbiota, in addition to distinct constituents of bile and mucus.…”
Section: Mouse Models For Enteropathogen Infectionmentioning
confidence: 99%
“… 133 In addition to their function in bacterial motility, C. jejuni utilizes flagella for protein secretion, biofilm formation, and adhesion. 134 , 135 Flagellar motility of C. jejuni is associated with a chemotaxis system, which is essential for effective colonization in the avian and mammalian guts. C. jejuni displays a chemotactic response to amino acids and organic acids originating from either the host or the residual gut microbiota, in addition to distinct constituents of bile and mucus.…”
Section: Mouse Models For Enteropathogen Infectionmentioning
confidence: 99%
“…Despite these effects, knowledge relating to how infection with Campylobacter species results in these outcomes is limited. For example, because whole-genome analysis of C. jejuni isolates suggests the pathogen lacks many of the prototypical secretion systems and virulence factors often associated with pathogenesis, gastrointestinal disease is hypothesized to be due to dysregulated activation of the host immune response through a factor or process unique to C. jejuni (Ren et al, 2018). Since little work has been done to understand the host response to C. jejuni and its consequence on gastrointestinal health, our group previously examined and observed neutrophils are recruited to the colon of infected animals and that predominantly neutrophil-derived proteins are elevated in the feces of C. jejuni -infected patients.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies investigated host adaptation, especially from C. jejuni, as this species shows a well-defined lineage separation based on MLST data that distinguish the population into host-specialist and host-generalist clonal complexes (Sheppard et al 2014). Several colonization studies revealed that modification and differential transcription of motility genes in C. jejuni play a key role in adaptation and transmission (Hermans et al 2011;de Vries et al 2017;Ren et al 2018). These data were supported by in vitro experiments as well as by genomic data and by RNA sequencing.…”
Section: Source Attribution In Clinical and Agricultural Settingmentioning
confidence: 93%